2008
DOI: 10.1088/0957-4484/19/22/225706
|View full text |Cite
|
Sign up to set email alerts
|

Stable field emission performance of SiC-nanowire-based cathodes

Abstract: In this paper we report the fabrication and testing of diode-type low-voltage field emission display (FED) devices with SiC-nanowire-based cathodes. The SiC-nanowire FEDs (flat vacuum lamps) were characterized by low emission threshold fields (∼2 V µm(-1)), high current density and stable long-term performance. The analysis of field emission data evidenced that the Schottky effect would have a considerable influence on the field emission from nanowire-based samples, leading to the true values of the field enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…This simple one-step technique, has demonstrated efficient SiC cold cathodes that have a lower turn-on field (1.8-2.2 V/μm) than their Si-based counterparts (2.7-3.3 V/μm) and that are able to yield higher current densities at a given operation voltage [76]. Moreover, Kim et al [77] reported the fabrication of, diode-type, field-emission-display (FED) devices with 3C-SiC NWs-based cathodes, which also demonstrated excellent FE properties at low applied voltages/electric fields and stable long-term performance. SiC nanowires coated with an optimized SiO2 thickness have higher field emission current than the bare SiC nanowires [41].…”
Section: Field Emission Cathodesmentioning
confidence: 99%
See 1 more Smart Citation
“…This simple one-step technique, has demonstrated efficient SiC cold cathodes that have a lower turn-on field (1.8-2.2 V/μm) than their Si-based counterparts (2.7-3.3 V/μm) and that are able to yield higher current densities at a given operation voltage [76]. Moreover, Kim et al [77] reported the fabrication of, diode-type, field-emission-display (FED) devices with 3C-SiC NWs-based cathodes, which also demonstrated excellent FE properties at low applied voltages/electric fields and stable long-term performance. SiC nanowires coated with an optimized SiO2 thickness have higher field emission current than the bare SiC nanowires [41].…”
Section: Field Emission Cathodesmentioning
confidence: 99%
“…SiC NWs also present concrete advantages for forming field emission cathodes since apart their high aspect ratio, they present low electron affinity value and excellent chemical and physical stability [12]. Finally, SiC NWs are very attractive for thermoelectric applications due to, from one hand, the excellent thermoelectric properties of bulk SiC [13] and on the other hand, the recent-theoreticalprediction of 100-times reduction of the thermal conductivity at the nanoscale, due to the increased role of phonon scattering, will lead to an even more increased thermoelectric figure of merit ZT [14].…”
Section: Introductionmentioning
confidence: 99%
“…One-dimensional (1D) SiC nanomaterials have attracted much attention because of their versatile electrical, optical and mechanical properties compared to their bulk counterparts [1][2][3]. These unique properties make 1D SiC nanomaterials suitable for various applications in electronic nanodevices [4,5], optoelectronic nanodevices [5,6], field-emission devices [7,8], nanocomposites [1,9], photocatalysts [10], hydrogen storage [11], and hydrophobic devices [12].…”
Section: Introductionmentioning
confidence: 99%
“…Field emission (FE), is one of the main features of 1D nanostructures, and is of great commercial interest in displays and other electronic devices. Up to now, FE characteristics based on various 1D nanostructures, such as SiC nanowires/nanobelts/nanocables [9][10][11][12][13], CNTs (carbon nanotubes) [8], ZnO nanowires/nanobelts [14][15][16], ZnS nanobelts [17,18], Si nanowires [19,20], WO 3 nanowires [21], Fe 2 O 3 nanoneedle arrays [22], and B nanowire arrays [23] have been widely investigated. For a given material, it has been demonstrated that the material with high aspect ratio, sharp tips, and abundant edges can greatly increase FE performance [21].…”
Section: Introductionmentioning
confidence: 99%